Território, Estado e poder econômico: concessão de gás canalizado no estado de São Paulo e ação da empresa Compass Gás & Energia S.A. - Oliveira, Larissa Gabriella Silva [UNESP] (Universidade Estadual Paulista (Unesp), 2022)
The territory used constitutes, historically, the inseparable set of actions of the actors involved - State and private institutions - in the territory, the materialization of actions, whether they are movements of society and industrial and service dynamics. Thus, the link between firms and the State modified the dynamics of the territory, being constituted by its agents and its stages in the current phase of capitalism, which we can analyze the national space within the international economy, that is, the use of space according to the resources and information available that the hegemonic agents have to act according to their interests. And, in view of this, we can notice the differentiation of the territories according to how the actors carry out their operations in a portion of the space, with a competition between the places. The domination of these agents in the territory demonstrates the character of "borderless" capitalism, where it is the phase that multinational corporations short-circuit the states, applying the so-called "external management of territories" (Santos, 2000), that is, the external execution in national territories. With this, we can question the role of private institutions and their interests before the policies of national states, which, in turn, are responsible for ensuring social welfare and guaranteeing the designs of multinational corporations in order to insert themselves in the dynamics of globalization. Thus, we propose to analyze the dynamics of private companies in national territories, especially the concession of piped gas in São Paulo and the performance of the corporation Compass Gas & Energy SA in the dispute to acquire more influence in the management of differentiated territories according to their wishes. In addition, the socio-spatial implications and changes in the Brazilian natural gas market after the New Regulatory Framework of 2020 presented by the federal government, which contributes to an even greater competition in the use of territory by the concessionaires, also come into question. This is a demonstration of the phenomenon of the ingression of national politics in the dynamics of the international economy structure, which causes changes in the use of territory by economic agents and, in this process, the State, as a liberal agent of spatiality, has a fundamental role, in view of the fact that it articulates the national projects according to the particular attractions of the companies, providing the functioning of the event. To investigate this dynamic in depth is also to make available some perspectives on the dynamics of the use of territory in the current phase of capitalism.

O território usado constitui-se, de forma histórica, o conjunto indissociável de atuações dos atores envolvidos – Estado e instituições privadas – no território, a materialização das ações, sejam elas movimentos da sociedade e dinâmicas industriais e de serviços. Assim sendo, o vínculo de firmas e Estado modificou as dinâmicas do território, sendo constituído por seus agentes e suas etapas na fase vigente do capitalismo, a qual podemos analisar o espaço nacional dentro da economia internacional, ou seja, a utilização do espaço conforme os recursos e as informações disponíveis que os agentes hegemônicos possuem para atuarem de acordo com seus interesses. E, diante disso, pode – se notar a diferenciação dos territórios conforme os atores concretizam suas operações em uma porção do espaço, havendo uma competitividade entre os lugares. A dominação desses agentes no território demonstra o caráter do capitalismo “sem fronteiras”, onde é a fase que as corporações multinacionais curto – circuitam os Estados, aplicando a chamada ‘gestão externa de territórios’ (Santos, 2000), ou seja, a execução externa nos territórios nacionais. Com isso, podemos questionar a atuação das instituições privadas e seus interesses perante as políticas dos Estados nacionais, estes, por sua vez, sendo responsáveis por assegurar o bem-estar social e garantir os desígnios das corporações multinacionais a fim de se inserir nas dinâmicas da globalização. Dessa forma, propomos analisar as dinâmicas das empresas privadas nos territórios nacionais, em destaque à concessão do gás canalizado em São Paulo e a atuação da corporação Compass Gás & Energia S.A na disputa para adquirir mais influência na gestão de territórios diferenciados conforme seus anseios. Além disso, também entra em questão as implicações socioespaciais e as mudanças no mercado de gás natural brasileiro após o Novo Marco Regulatório de 2020 apresentado pelo governo federal, o qual contribui para uma competição ainda maior no uso do território por parte das concessionárias. Isso é uma demonstração do fenômeno da ingressão da política nacional nas dinâmicas da estrutura da economia internacional, em que provoca alterações no uso do território pelos agentes econômicos e, nesse processo, o Estado, como agente liberal da espacialidade, possui um papel fundamental, tendo em vista que articula os projetos nacionais conforme os atrativos particulares das empresas, proporcionando o funcionamento do evento. Investigar essa dinâmica em profundidade é também disponibilizar algumas perspectivas sobre as dinâmicas do uso do território na atual fase do capitalismo.
Territory, State and economic power: concession of piped gas in the state of São Paulo and action of the company Compass Gás & Energia S.A.
Keywords: Exploration of public service; Concession; Piped natural gas; Geografia econômica; Concessões administrativas; Distribuição de gás; Território ocupado